Geopolitica vaticana, istituzioni politiche e ordinazioni episcopali nella Repubblica Popolare Cinese. Riflessioni in tema di rapporti tra Stato e Chiesa (Stato, Chiese e pluralismo confessionale, 2023)
Vatican geopolitics, political institutions and episcopal ordinations in the People's Republic of China. Reflections on State-Church RelationsABSTRACT: The agreement between the Holy See and the People's Republic of China, concluded in 2018 ad experimentum, has been extended until 31-12-2024.Relations between the Vatican and the Holy See do not follow a linear trend, due to the recurring attempts of some Chinese clergy-so-called patriot clergy-to accept appointments as Diocesan Ordinary without the mandate of the Holy See. In such cases, the relevant regulatory provisions entail excommunication latae sententiae. This contribution, analysing some historical precedents such as the struggle for the endowments and the separation of the constitutional clergy in the period of the French Revolution, proposes an interpretation of the events to understand the Holy See's attitude in the remission of the excommunication to the patriot bishops: the realisation that Catholicism was no longer a phenomenon limited to the European world. The centre of gravity of the Church's influence is irreversibly declining towards non-European areas.SOMMARIO: 1. Premessa - 2. Introduzione al tema - 3. Ius publicum ecclesiasticum sinicum - 4. L’accordo del 2018 tra Santa Sede e Repubblica Popolare Cinese - 5. Il primo quadriennio di applicazione. Riflessioni critiche - 6. Storia e controstoria - 7. Le radici medievali dei rapporti tra Chiesa e Stato: tra Gregorio VII ed Enrico IV - 8. L’età moderna. Le aperture del vescovo G.B. Chiaramonti per una 'democrazia cristiana'. Gli 'articoli organici' del periodo napoleonico - 9. Storia e modernità nelle relazioni tra Chiesa e Repubblica Popolare Cinese.